CRISPR/Cas9 directed to the Ube3a antisense transcript improves Angelman syndrome phenotype in mice - Ralf S. Schmid; Xuefeng Deng; Priyalakshmi Panikker; Msema Msackyi; Camilo Breton; James M. Wilson (The Journal of Clinical Investigation, 2021)
Gene editing holds the potential to correct mutations and cure devastating genetic disorders. The technology has not yet proven efficacious for therapeutic use in CNS diseases with ubiquitous neuronal defects. Angelman syndrome (AS), a severe neurodevelopmental disorder, is caused by a lack of maternal expression of the UBE3A gene. Because of genomic imprinting, only neurons are affected. One therapeutic approach focuses on the intact paternal UBE3A copy in patients with AS that is silenced by an antisense transcript (UBE3A-ATS). We show here that gene editing of Ube3a-ATS in the mouse brain resulted in the formation of base pair insertions/deletions (indels) in neurons and the subsequent unsilencing of the paternal Ube3a allele in neurons, which partially corrected the behavioral phenotype of a murine AS model. This study provides compelling evidence to further investigate editing of the homologous region of the human UBE3A-ATS because this may provide a lasting therapeutic effect for patients with AS.